Alcohol use among university students in Sweden measured by an electronic screening instrument - Ekman Diana; Ölvander Christina; Wiréhn Ann-Britt; Andersson Agneta; Bendtsen Preben (BMC, 2009)
Abstract Background Electronic-based alcohol screening and brief interventions for university students with problem drinking behaviours forms an important means by which to identify risky drinkers. Methods In this study an e-SBI project was implemented to assess drinking patterns, and to provide personalised feedback about alcohol consumption and related health problems, to students in a Swedish university. In this study, third semester university students (n = 2858) from all faculties (colleges) at the University were invited to participate in e-SBI screenings. This study employed a randomised controlled trial, with respondents having a equal chance of being assigned to a limited, or full-feedback response. Results The study shows that high risk drinkers tend to underestimate their own consumption compared to others, and that these high risk drinkers experience more negative consequences after alcohol intake, than other respondents. There was a strong belief, for both high- and low-risk drinkers, that alcohol helped celebrations be more festive. This study also confirms findings from other study locations that while males drank more than females in our study population; females reached the same peak alcohol blood concentrations as males. Conclusion Obtaining clear and current information on drinking patterns demonstrated by university students can help public health officials, university administration, and local health care providers develop appropriate prevention and treatment strategies.